?EFFECT OF DIFFERENT DOMESTIC PROCESSING AND COOKING METHODS ON THE TANNIN CONTENTS OF LENTILS (LENS ESCULENTA) (Biological Sciences - PJSIR, 1996)
Significant reduction in tannin contents was observed after soaking the lentils in simple water or salt solu- tions of different concentrations. Soaking in sodium bicarbonate solution was the most effective way to reduce the tannin content. Cooking lentils also further reduced tannin and improved protein digestibility.